Geopolitics of translation in soviet Cuba: from marxist aesthetics to socialist literary boom - Punales-Alpizar, Damaris (Revista de Letras, 2019)
In Cuba, literature from socialist countries played a transcendental role in the formation of the literary system from the sixties to the nineties. Thousands of books written in socialist countries, in Spanish translation, circulated in the island. This literature put the Cuban reader in contact with an exceptional cultural archive, provided literary models, and informed about what could be published in a socialist society. Access to this type of literature followed cultural/editorial policies from both countries: the issuer and the receiver. Editorial decisions responded in many cases to geopolitics positions and led to a socialist literary boom supported and funded by the State.